2010
DOI: 10.1002/cmdc.200900444
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chemical Modifications for siRNA Therapeutics: A Structural and Functional Outlook

Abstract: RNA interference (RNAi) is a post-transcriptional gene silencing mechanism induced by small interfering RNAs (siRNAs) and micro-RNAs (miRNAs), and has proved to be one of the most important scientific discoveries made in the last century. The robustness of RNAi has opened up new avenues in the development of siRNAs as therapeutic agents against various diseases including cancer and HIV. However, there had remained a lack of a clear mechanistic understanding of messenger RNA (mRNA) cleavage mediated by Argonaut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
143
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(145 citation statements)
references
References 227 publications
(495 reference statements)
1
143
0
1
Order By: Relevance
“…At the beginning this approach was proposed as a way to increase nuclease resistance of siRNA in the presence of serum, in the cells and bloodstream [61,62]. The enhancement of nuclease resistance of siRNA by chemical modification not resulting in the drop of its silencing activity represent a complex task, since silencing activity of siRNA is strongly affected by the nature, number and locations within the duplex of chemical modifications [65,76,181]. Despite many works carried out in this area, a general algorithm which allows receiving active nuclease resistant siRNA is not developed yet.…”
Section: Resultsmentioning
confidence: 99%
“…At the beginning this approach was proposed as a way to increase nuclease resistance of siRNA in the presence of serum, in the cells and bloodstream [61,62]. The enhancement of nuclease resistance of siRNA by chemical modification not resulting in the drop of its silencing activity represent a complex task, since silencing activity of siRNA is strongly affected by the nature, number and locations within the duplex of chemical modifications [65,76,181]. Despite many works carried out in this area, a general algorithm which allows receiving active nuclease resistant siRNA is not developed yet.…”
Section: Resultsmentioning
confidence: 99%
“…Tissues containing silencing RNA may be used in the possible heart transplantation in animal models (Negishi et al, 2008). In comparative studies it was observed that silencing RNA labeled with fluorescent administered rectal and intra-peritoneal significant uptake was observed in the rectal administration after 4 hours of the dosing (Shukla et al, 2009). This study showed that silencing RNA was useful in tissue retaining but proteins were not studied.…”
Section: Modalities For Delivering Silencing Rna To Kidneymentioning
confidence: 99%
“…These include low efficacy of mRNA inhibition, off targets, immunogenicity, low serum stability against the nucleases, cell specific delivery problems, target site recognition, accessibility and its cleavage. [7][8][9] To overcome most of these shortcomings, siRNA molecules are engineered by introducing chemical modifications. 9,10 Natural RNAs comprises of ribonucleotide-moieties, composed of sugar (Ribose), phosphate (phosphodiester bond) and nitrogenous bases Adenine (A), Guanine (G), Cytosine (C), and Uracil (U).…”
Section: Introcuctionmentioning
confidence: 99%
“…11 With modifications on these constituent molecules, sphere of their functionality has been enhanced. 8 Numerous studies on chemical modifications directed on siRNAs are reported in the literature aimed to improve their therapeutic potential. 6 Testing different chemical modifications at different positions and their combinations on siRNAs are vast.…”
Section: Introcuctionmentioning
confidence: 99%